Exploring the patterns and influencing factors of emerging technology impact: a case study of digital medical technology - Man Jiang; Siluo Yang; Shuang Tao (Information Research: An International Electronic Journal)
Introduction. Impact, as an intrinsic attribute of emerging technologies, plays a crucial role in their identification and understanding. Traditional citation metrics, while reflective of impact magnitude, fail to explain its nature.